A chemical titration method for quantification of carbenes in Mo- or W-containing catalysts for metathesis of ethylene with 2-butenes: verification and application potential. Issue 20 (3rd October 2019) - Otroshchenko, Tatiana; Reinsdorf, Ole; Linke, David; Kondratenko, Evgenii V.
Abstract : We introduce and experimentally validate a simple titration method for quantifying the number of carbenes acting as active sites in the metathesis of ethylene with 2-butenes over Mo- or W-containing catalysts. Abstract : We introduce and experimentally validate a simple titration method for quantifying the number of carbenes acting as active sites in the metathesis of ethylene with 2-butenes over Mo- or W-containing catalysts. This method is based on the experimentally proven mechanistic sequence of carbene formation through the reaction of ethylene with oxidized metal oxide species: (i) reduction of M(vi ) to M(iv ) by ethylene, (ii) addition of ethylene to M(iv ) to yield MC2 H4 carbene and (iii) transformation of the latter to MCH2 upon reaction with C2 H4 yielding C3 H6 . As MCH2 cannot produce C3 H6 when reacting with C2 H4, the amount of C3 H6 formed in step (iii) corresponds to the number of catalytically active carbenes. The applicability of this method was supported by establishing a correlation between this number and the steady-state rate of propene formation in the metathesis of ethylene with 2-butenes.